2003
DOI: 10.1097/01.ju.0000067446.17576.bd
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Effect of Acute Transcutaneous Posterior Tibial Nerve Stimulation in Overactive Bladder

Abstract: These results suggest an objective acute effect of posterior tibial nerve stimulation on urodynamic parameters. Improved bladder overactivity is an encouraging argument to propose posterior tibial nerve stimulation as a noninvasive treatment modality in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
130
0
47

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(188 citation statements)
references
References 20 publications
9
130
0
47
Order By: Relevance
“…Mais recentemente, a eletroestimulação do nervo tibial (ENT) no tratamento da BH vem sendo estudada e discutida com eletrodos de inserção (subcutâneos) e superficiais, demonstrando resultados favoráveis, constituindo-se uma opção nos casos de contraindicação ou intolerância à ET [15][16][17] . Entretanto, a repercussão da ENT sobre a QV de mulheres com BH tem sido pouco estudada e parece não haver estudos que comparem a repercussão desse tratamento com o tratamento de ET.…”
Section: Introductionunclassified
“…Mais recentemente, a eletroestimulação do nervo tibial (ENT) no tratamento da BH vem sendo estudada e discutida com eletrodos de inserção (subcutâneos) e superficiais, demonstrando resultados favoráveis, constituindo-se uma opção nos casos de contraindicação ou intolerância à ET [15][16][17] . Entretanto, a repercussão da ENT sobre a QV de mulheres com BH tem sido pouco estudada e parece não haver estudos que comparem a repercussão desse tratamento com o tratamento de ET.…”
Section: Introductionunclassified
“…Percutaneous tibial nerve stimulation (PTNS) consists of transcutaneous electrical stimulation with the aid of needle electrodes in the posterior tibial nerve region 4,[10][11][12][13] . Although it was proposed more than 20 years ago, the details of the action mechanism of PTNS are not fully known 14,15 . It has been suggested that this form of electrical stimulation inhibits bladder activity by the depolarization of sacral and lumbar somatic afferent fibers 14,15 that results from motor and sensory responses to stimuli in the posterior tibial nerve region.…”
Section: Introductionmentioning
confidence: 99%
“…Nöromodülasyon nörojenik ve nörojenik olmayan alt üriner sistem disfonksiyonu tedavisinde intravezikal elektriksel stimülasyon, direk mesane stimülasyonu, pelvik sinir stimülasyonu, pudendal sinir stimülasyonu, sakral spinal stimülasyon, dorsal rizotomi ile birlikte sakral anterior kök stimülasyonu, uyluk kaslarının elektriksel stimülasyonu, posterior tibial sinir stimülasyonu ve TENS (suprapubik veya S2-S3 dermatomlarına) gibi birçok değişik teknik ve cihazlarla uygulanmaktadır (4,14,(17)(18)(19)(20)(21)(22). S3 segmental sinir köklerinin cerrahi yöntemlerle implante edilen elektrotlarla direkt elektriksel stimülasyonu sonucu nörojenik detrüsör aşırı aktivitesinde başarılı sonuçlar alınması, daha kolay uygulanabilen, invaziv olmayan, belirgin yan etkisi bulunmayan, tedavi maliyeti daha düşük bir yöntem olan S3 dermatomuna yüzeyel elektrotlar ile TENS uygulamasını gündeme getirmiştir (4-7).…”
Section: Discussionunclassified